2017
DOI: 10.3390/nu9010049
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Dish-Based Semiquantitative Food Questionnaire in Rural Bangladesh

Abstract: A locally validated tool was needed to evaluate long-term dietary intake in rural Bangladesh. We assessed the validity of a 42-item dish-based semi-quantitative food frequency questionnaire (FFQ) using two 3-day food diaries (FDs). We selected a random subset of 47 families (190 participants) from a longitudinal arsenic biomonitoring study in Bangladesh to administer the FFQ. Two 3-day FDs were completed by the female head of the households and we used an adult male equivalent method to estimate the FD for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 43 publications
16
44
2
Order By: Relevance
“…Generally, FFQs are used for ranking individuals according to food or nutrient intake rather than for estimating absolute amounts of intake. In this regard, we used cross-classification analysis whose results for the majority of nutrients were promising, in which approximately more than 60% of participants were classified in the correct quartiles, which is consistent with other studies [12,20,26].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Generally, FFQs are used for ranking individuals according to food or nutrient intake rather than for estimating absolute amounts of intake. In this regard, we used cross-classification analysis whose results for the majority of nutrients were promising, in which approximately more than 60% of participants were classified in the correct quartiles, which is consistent with other studies [12,20,26].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it is very challenging, if not impossible, to estimate usual intake of single ingredients through an FFFQ. Several international studies have developed DFFQs for epidemiological studies [3,16,20]. However, there were some limitations namely not considering seasonal variations of foods [3], the generalizability [16,20], and the gold standards affairs which have limited their usage as a valid tool.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a moderate to good correlation for almost all food groups according to the previous cutoff point (5). This is in good agreement with previous validation studies assessing food group intakes (8,10,19,20). The good correlation found for vegetable intakes in our study is higher than those reported by other validation studies (8,10,12).…”
Section: Discussionsupporting
confidence: 91%
“…FFQ showed a fair quartile classi cation agreement for cereals, legumes, and roots and tubers (K values 0.2-0.6). Similarly, other studies reported a fair classi cation agreement for this particular food group (13,19). For beverage intake, our study indicated a misclassi cation (30.5%) into opposite quartile supported by low kappa value (k value <0.2) showing the poor outcome.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation